Assessment of Serum Interleukin-27 and Mean Platelet Volume in Late-Onset Neonatal Sepsis - Tosson, Angie M. S.; Koptan, Dina M. T.; Kamal, Mohamed; Abd Elhady, Marwa (American Journal of Perinatology, 2022)
Objective Late-onset sepsis (LOS) is a substantial contributor to morbidity and mortality among neonates. The use of nonculture-based tools for early diagnosis is an area of active investigation. Therefore, we aimed to evaluate the diagnostic value of serum interleukin-27 (IL-27) and mean platelet volume (MPV) in full-term neonates with LOS.Study Design In this single-center, cross-sectional study, 90 full-term newborns were assigned to two equal-matched groups as follows: (1) culture-proven sepsis and (2) control groups. Clinical data and laboratory findings as complete blood pictures, including MPV, highly sensitive C-reactive protein, and blood culture results, were recorded. Moreover, IL-27 levels were measured using enzyme-linked immunosorbent assay.Results IL-27 levels (median = 4,364 pg/mL) and MPV (mean = 12.02 ± 1.54 FL) were significantly higher in the culture-proven sepsis group than in the control group (p < 0.001). For IL-27, the optimum cut-off value for the diagnosis of LOS was 283.8 pg/mL with sensitivity and specificity of 97.8 and 100%, respectively. For MPV, the optimum cut-off value was 11.6 FL, with diagnostic sensitivity and specificity of 77.8 and 97.8%, respectively.Conclusion IL-27 and MPV are promising markers for the diagnosis of LOS in full-term neonates. The diagnostic performance of IL-27 was superior to MPV.Key Points
Keywords: interleukin-27; late-onset neonatal sepsis; mean platelet volume; nonculture-based markers